UJI ANTIOKSIDAN DAN KUALITAS ORGANOLEPTIK SEDUHAN TEH Acanthus ilicifolius DAN Rhizophora apiculata - Putri, Serina; Prayitno, Dwi Imam; Minsas, Sukal; Idiawati, Nora (Indonesian Journal of Pure and Applied Chemistry, 2026)
The use of mangrove leaves in functional beverages is increasingly popular due to their bioactive compounds, which have potential as natural antioxidant sources. This study aimed to analyze the antioxidant activity and organoleptic quality of tea infusions prepared from Acanthus ilicifolius and Rhizophora apiculata leaves. Leaf samples were collected from the coastal area of Kubu Raya Regency, vacuum-dried, ground, and prepared as tea infusions. Antioxidant activity was determined using the DPPH method, while organoleptic quality (appearance, aroma, and taste) was evaluated through a hedonic test with 10 panelists. The results revealed that A. ilicifolius tea exhibited higher antioxidant activity, with an IC₅₀ of 9.48 ppm, compared to R. apiculata at 16.36 ppm. Both values fall into the very strong category (IC₅₀